Antenatal Care Education as an Initial Step Toward Maternal and Child Well-Being - Br Ginting Munthe, Novita; Sembiring, Iskandar Markus (JURNAL PENGMAS KESTRA (JPK), 2025)
Maternal and infant mortality remain significant public health challenges in Indonesia, particularly in rural areas where awareness and access to healthcare are limited. This community service aimed to improve pregnant women’s understanding of the importance of antenatal care (ANC) as a preventive measure to enhance maternal and child well-being. The program was conducted at Klinik Pratama Rawat Inap Mars Deli Serdang and involved 35 pregnant women. Education was delivered through direct counseling sessions that included materials on ANC visit schedules, early detection of pregnancy complications, nutrition, and birth preparedness. Pre- and post-tests were used to evaluate changes in knowledge and attitudes. The results show a marked increase in the participants’ understanding of ANC, with a rise in knowledge from 40% to 88% after the session. Participants expressed greater motivation to attend routine ANC visits and actively engaged in discussions. The findings suggest that community-based education significantly enhances awareness and fosters positive behavioral change regarding ANC compliance. Collaboration between healthcare professionals, clinics, and academic institutions is crucial to sustain and expand such initiatives for long-term maternal and child health improvement.